ANALISIS PENYUSUNAN BAHAN BAKU PANGAN PADA UKM TBK LEGENDA: ANALISIS PENYUSUNAN BAHAN BAKU PANGAN PADA UKM TBK LEGENDA - Khairi, Imala Tunil; Asmarawati, Citra Indah (Computer Science and Industrial Engineering, 2024)
As a developing country, Indonesia seeks to carry out economic development in a planned and gradual manner. Economic development seeks to achieve high levels of individual business growth which ultimately enables the creation of small and medium enterprises (SMEs). However, one of the problems that often occurs in this industry is the irregular arrangement of goods, where when customers need goods, the goods are difficult to find, causing losses to the company. The ABC (Active Based Costing) method is the right method to handle this problem where the classification is divided into several categories. In comparison between the initial layout and the proposal, there is a significant difference in value where the initial Material Handling Cost (OMH) for category A is Rp.17,289,090.25, while for Material Handling Costs (OMH) the proposed category A is I Rp. 5,090,676,57. the value is lower than the initial one...